Factors Influencing Students’ Satisfaction and Continuance Intention to Use B2C Online Shopping Platform in a University in Sichuan, China - Sun, Yan (Scholar: Human Sciences, 2025)
Purpose This study aims to explore the factors that affect the satisfaction and continuous intention of Chinese college students using B2C shopping platforms. The scope of this study focuses on 545 first- and second-year students in Sichuan Architecture Vocational and Technical College. Research design, data, and methodology: This study was quantitative, in which samples were selected using multi-stage sampling techniques such as judgment, quota, and convenience sampling. The research adopts the questionnaire survey method, which is this paper’s data collection tool. This study is to explore the relationship between seven variables. Confirmatory factor analysis and structural equation modeling were used to evaluate the service quality, perceived value, usefulness, convenience, trust, satisfaction, and continuous intention of B2C online shopping platforms. Results: Convenience, perceived value, service quality, trust, and perceived usefulness, significant influence satisfaction. Moreover, perceived usefulness and satisfaction significantly influence continuance intention. Conclusions: As a generation growing up with the development of network technology, college students have become an extremely important part of the online shopping group. This paper analyzes and understands consumer behaviors from the perspective of college students and the factors that affect their satisfaction and sustainable intention and puts forward feasible opinions and suggestions for online platform merchants.